Functional outcome of routine versus on-demand removal of the syndesmotic screw: a multicentre randomized controlled trial. (1st November 2021) - Sanders, Fay R. K.; Birnie, Merel F.; Dingemans, Siem A.; van den Bekerom, Michel P. J.; Parkkinen, Markus; van Veen, Ruben N.; ,; Goslings, J. Carel; Schepers, Tim
Abstract : Aims: The aim of this study was to investigate whether on-demand removal (ODR) is noninferior to routine removal (RR) of syndesmotic screws regarding functional outcome. Methods: Adult patients (aged above 17 years) with traumatic syndesmotic injury, surgically treated within 14 days of trauma using one or two syndesmotic screws, were eligible (n = 490) for inclusion in this randomized controlled noninferiority trial. A total of 197 patients were randomized for either ODR (retaining the syndesmotic screw unless there were complaints warranting removal) or RR (screw removed at eight to 12 weeks after syndesmotic fixation), of whom 152 completed the study. The primary outcome was functional outcome at 12 months after screw placement, measured by the Olerud-Molander Ankle Score (OMAS). Results: There were 152 patients included in final analysis (RR = 73; ODR = 79). Of these, 59.2% were male (n = 90), and the mean age was 46.9 years (SD 14.6). Median OMAS at 12 months after syndesmotic fixation was 85 (interquartile range (IQR) 60 to 95) for RR and 80 (IQR 65 to 100) for ODR. The noninferiority test indicated that the observed effect size was significantly within the equivalent bounds of -10 and 10 scale points (p < 0.001) for both the intention-to-treat and per-protocol, meaning that ODR was not inferior to RR. There were significantly more complications in the RR group (12/73) than in the ODR group (1/79) (p = 0.007). Conclusion: ODR of the syndesmotic screw is not inferior to routine removal when it comes to functional outcome. Combined with the high complication rate of screw removal, this offers a strong argument to adopt on demand removal as standard practice of care after syndesmotic screw fixation. Cite this article: Bone Joint J  2021;103-B(11):1709–1716.